ANALISIS PENETAPAN HARGA JUAL PRODUK MARKISA PADA PT. TORAJA MARKISA DI TANA TORAJA - Asri Nur Muin (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2011)
The purpose of this research is to find methods of determining the selling price of the product at PT. Passion Fruit and Toraja To find an increase in sales at PT. Toraja Passion from year to year. The research uses two types of data Quantitative Data, is a type of data in the form of figures obtained from the company and qualitative data, is the type of data that is not in the form of numbers, both orally and in writing. The results showed that the selling price per bottle has increased over the years 2006 to 2010 compared to 2006 ie, where in 2003 the selling price rose by Rp. 500 or 11%, in 2008 prices rose by Rp. 500 or 10%, in 2009 prices increased by Rp. 500 or 9% and in 2010 prices rose again to Rp. 500 or 83% and the number of sales also increased from 2006 to 2010 compared to 2006 ie in the year 2007 the number of sales increased by Rp. 109 million or 21.1% and in 2004 the number of sales increased by Rp. 126.8 million or 16.3% and in 2009 the number increased penjulan Rp. 136.4 million or 7.58% and in 2010 the total sales of Rp. 154.8 million or 13.4%. This proves that the pricing set by PT. Passion Toraja have been effective.